International drive to illuminate delirium: A developing public health blueprint for action - Cunningham, Colm (My University, 2020)
Presently, there is a clear societal and demographic imperative to identify and deliver interventions that are effective in reducing dementia. With the high failure rate of compounds in clinical trials, and with pharmaceutical development cycles typically lasting decades, a hybrid person-with-dementia-centered approach that precisely inte- grates pharmaceutical, non-pharmaceutical, lifestyle modification, and care interventions for the individual may offer more immediate results for reducing dementia burden. One important, tangible, and overlooked strategy with this proposed approach may be through the recognition and prevention of delirium.
PUBLISHED
cited By 5
Keywords: hybrid person-with-dementia-centered; Delirium; alzheimer